PUBLIC INTEREST, STATE CONTROL, AND PROPORTIONAL COMPENSATION: CONSTITUTIONAL TENSIONS IN INDONESIA'S LAND ACQUISITION REGIME - Rosmidah Rosmidah; Adeb Davega Prasna; Arjun Deswal (Faculty of Law, Universitas Lampung, 2026)
This article examines normative distortions arising from the expanded meaning of public interest in land acquisition policies in Indonesia and their impact on compensation proportionality. Data from the Agrarian Reform Consortium show that infrastructure-related agrarian conflicts rose from 212 cases in 2022 to 241 in 2023, indicating that compensation mechanisms fail to meet substantive justice. Using a normative juridical approach with conceptual and constitutional analysis, this article argues that the expansion of public interest under Law No. 2 of 2012, including investment and National Strategic Projects, has weakened proportionality. Compensation has shifted from full restitution of community losses to limited replacement of physical land and assets. This shift fails to satisfy key proportionality requirements: suitability of purpose, necessity of means, and balance between public benefit and individual burden, as mandated by Article 33 of the 1945 Constitution. The article concludes that without redefining the constitutional limits of public interest, land acquisition will continue to favor economic interests at the expense of citizens’ rights, particularly those of indigenous communities.